Effects of Co/Si Atomic Ratio on Hardness and Electrical Conductivity of Cu–Co–Si Alloys. Issue 6 (26th October 2022) - Zhao, Feng; Lei, Chenhui; Yu, Jian; Yang, Huiya; Ling, Guoping; Liu, Jiabin; Huang, Liuyi; Wang, Hongtao
Abstract : Cu–Co–Si alloys are being intensively studied as alternative candidates for Cu–Ni–Si alloys for integrated circuit lead frames. However, the effects of different precipitate types on the comprehensive properties of Cu–Co–Si alloys are not clear. Herein, several Cu–Co–Si alloys with various precipitates (CoSi, Co2 Si, and Co) are designed based on phase diagrams calculation. The designed alloys are melted, cold‐rolled, and aged to test the corresponding hardness and electrical conductivity (EC). X‐ray diffraction and transmission electron microscopy are utilized to analyze the precipitates generated in those alloys. In the alloys with Co/Si ≤ 1, the excess Si atoms are not easy to precipitate from the copper lattice after CoSi precipitation, which seriously damages the EC. Co‐precipitation in alloys with Co/Si > 2 is beneficial to improve EC without sacrificing hardness. According to thermodynamic calculation, precipitates in Cu‐1.62Co‐0.35Si (wt%) alloy with total elements between 1.5 and 2.0 wt% are all Co2 Si and have the highest mass fraction in the equilibrium state. The different precipitates are highly dependent on the Co/Si atomic ratio and essential to Cu–Co–Si alloys' mechanical and electrical performances. Abstract : Herein, the precipitate types and properties of Cu–Co–Si alloys with different Co/Si atomic ratios are discussed. Several Cu–Co–Si alloys are designed with computational phase diagrams, and their precipitate types are analyzed by X‐ray diffraction (XRD) and transmission electron microscopy (TEM).